2017
DOI: 10.3390/nu9091016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-Glucans Ingestion on Alveolar Bone Loss, Intestinal Morphology, Systemic Inflammatory Profile, and Pancreatic β-Cell Function in Rats with Periodontitis and Diabetes

Abstract: This study aimed to evaluate the effects of β-glucan ingestion (Saccharomyces cerevisiae) on the plasmatic levels of tumor necrosis factor-α (TNF-α) and interleukin-10 (IL-10), alveolar bone loss, and pancreatic β-cell function (HOMA-BF) in diabetic rats with periodontal disease (PD). Besides, intestinal morphology was determined by the villus/crypt ratio. A total of 48 Wistar rats weighing 203 ± 18 g were used. Diabetes was induced by the intraperitoneal injection of streptozotocin (80 mg/kg) and periodontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…The presence of PD increased both glycaemia and HbA1c levels in rats not induced to DM, confirming the bidirectional relationship between DM and PD [ 43 ]. This behavior was observed in previous studies using both type 1 (single dose of strepozotocin) [ 44 , 45 ] and type 2 (obese diabetic Zucker rats) [ 46 ] using ligature-induced periodontitis models.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The presence of PD increased both glycaemia and HbA1c levels in rats not induced to DM, confirming the bidirectional relationship between DM and PD [ 43 ]. This behavior was observed in previous studies using both type 1 (single dose of strepozotocin) [ 44 , 45 ] and type 2 (obese diabetic Zucker rats) [ 46 ] using ligature-induced periodontitis models.…”
Section: Discussionsupporting
confidence: 78%
“…Besides, in human studies, it is difficult to control environmental and social variables to establish a cause effect measurement of treatment outcomes [ 49 ]. Ligature placement for 14 days results in marked alveolar bone loss [ 23 , 44 , 50 , 51 ]. When this ligature is placed in diabetic animals, alveolar bone loss tends to be worse, as observed in our study [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal studies have shown that an increased intake of dietary fiber can reduce the progression of periodontal disease [ 51 , 52 , 53 , 54 ]. In humans, a study involving 6052 adults also reported that low dietary fiber consumption was associated with worse periodontal status [ 55 ].…”
Section: Discussionmentioning
confidence: 99%